"Both men and beasts": Rereading Karen Blixen's anthropomorphisms. (8th July 2018) - Mortensen, Peter
Abstract: Danish author Karen Blixen's frequent use of human–animal comparisons in Out of Africa (1937) has been critically controversial ever since the early 1980s, when the Kenyan writer and critic Ngũgĩ wa Thiong'o cited this practice as evidence of Blixen's racist and dehumanizing portrayal of Africans. In this essay, I outline an alternative way of thinking about anthropomorphism and zoomorphism that is inspired by current theoretical developments in critical posthumanism, animal studies, new materialism, and ecocriticism. Reading the anthropomorphic/zoomorphic imagery that pervades Out of Africa, I endeavor to show that the premises underpinning Ngũgĩ's influential critique are precisely the problematic assumptions that Blixen labors to destabilize. As I interpret Blixen's textual maneuvers, these tropes function less to privilege some characters and dehumanize others along social and racial lines than to make it radically unclear exactly what the categories "human" and "animal" mean in her narrative world.